Increasing Learning Interests of PAUD Students Through Project Based Learning - Muammar Khadafi; Nurhasanah; Esti Rubiyat (Journal of Instructional Development, Innovation, and Evaluation, 2023)
This study aims to describe to Project based learning learning increase students. Project based learning is a learning model that uses projects/activities as media. Learners explore, assess, interpret, synthesize and information to produce various forms of learning outcomes. Interest in learning is a psychological aspect of a person that manifests itself in several symptoms, such as; passion, desire, feeling like to carry out the process of changing behavior through various activities which include seeking knowledge and experience. This research uses a qualitative descriptive with a phenomenological approach, which describes or describes the research object based on the facts that appear or as they are. so it is necessary to give full attention in learning and this attention because students feel happy and challenged to participate in learning activities in class. Factors of student interest in learning are influenced by internal factors and external factors. Students who have good physical and mental abilities and supportive environmental conditions can foster good student interest in learning. Project based learning very helpful in learning as it is today so that it can foster children's learning interest and children are increasingly motivated to learn.